Association between FTO gene polymorphism and productivity traits in Lithuanian pigs population - MIÐEIKIENË, R; PAKAÐIÛTË, I; BIÞIENË, R; PEÈIULAITIENË, N; MICEIKIENË, I; MAKÐTUTIENË, N; MORKÛNIENË, K (The Indian Journal of Animal Sciences, 2018)
FTO in pigs have reported associations of several single nucleotide polymorphisms with some fat-related traits. The purpose of our study was to investigate the FTO gene single nucleotide polymorphism (SNP) (g.400C>G) in the population of pigs and to evaluate the influence of polymorphism on productivity traits. This study of porcine FTO gene g.400C>G SNP was established from the isolated genomic DNA, amplified by nested polymerase chain reaction (PCR) and digested with restriction enzymes, then DNA fragments were separated by agarose gel electrophoresis. Allele C observed with frequency 0.4, allele G – 0.6. The most common genotype was GG, genotype CC was the rarest. CC genotype pigs consume the most feed per kilogram of weight gain compared with other genotypes. The highest values for backfat thickness at the last vertebra at Fat1 and Fat2 were observed in animals with genotype CC. The lowest muscularity (%) was also observed in CC genotype. It was found that almost all pig production traits were significantly influenced by breed. The breed and genotype interaction influence was statistically significant for muscularity of the carcasses and backfat at the Fat2 thickness.